Vídeo de animação sobre adaptação social para pessoas com estomias intestinais: um estudo metodológico - Silva, Breno Wagner Araújo Cosme da (2023)
Intestinal stoma is the name used when we refer to an opening in the abdomen artificially created by chirurgic procedure. After surgery, individuals usually face an adaptation process. Technologies focused on educational strategies on health, such as animated videos, can help patients during the adaptation period. This research aimed to develop and validate an animated video whose theme was the social adaptation of people with intestinal stoma. This is a methodological study carried out in three operational and standardized stages to the creation of educational movies: pre-production, production and post-production. We produced a screenplay based on the literature which approaches such topics as nutrition, self-image, selfcare and sexual activity. It portrays, in a simple and daily life way, a setting in which people using intestinal stoma meet a nurse for a group discussion. Each participant of the conversation shares their experiences, difficulties and achievements among the social adaptation they had to face for using an intestinal stoma. The screenplay was sent to a group of expert judges.We divided the analysis into two rounds using the Delphi technique with nurses (10 for the first round and 9 for the second round) and three specialists from the social communication area. To measure the agreement index between judges, we used the Content Validity Index (IVC). In the first evaluation with nurses, the reported IVC was 0,82, which was increased to 0,93 in the second round. As for the professionals of social communication, the IVC reported was 0,75 in the first moment and 0,85 in the second moment, which resulted in an index average higher than 0,78. After each round with the expert judges, we considered their comments on the screenplay and from their suggestions we updated our text. After that, we recorded the characters' voices and sent the files to a professional from the social communication area, who produced the video based on the screenplay. This animated video on the social adaptation of people who use the intestinal stoma, based on literature, was updated during the validation process. We concluded that it was possible to validate the animated video screenplay content with nine and ten nurses and three specialists from the social communication area by the increase of the IVC reported in both rounds.